2009
DOI: 10.7326/0003-4819-151-9-200911030-00151
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Testing and Pharmacologic Treatment of Erectile Dysfunction: A Clinical Practice Guideline From the American College of Physicians

Abstract: Published literature on this topic was identified by using MEDLINE (1966 to May 2007), EMBASE (1980 to week 22 of 2007), Cochrane Central Register of Controlled Trials (second quarter of 2007), PsycINFO (1985 to June 2007), AMED (1985 to June 2007), and SCOPUS (2006). The literature search was updated by searching for articles in MEDLINE and EMBASE published between May 2007 and April 2009. Searches were limited to English-language publications. This guideline grades the evidence and recommendations by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 191 publications
0
39
1
Order By: Relevance
“…In clinical trials, T replacement has consistently shown improvement in libido (22,30), whereas its efficacy in improving erectile dysfunction remains unclear (31). To our knowledge, no previous randomized controlled trial has assessed the efficacy of T replacement in men with low T and ejaculatory disorders.…”
Section: Discussionmentioning
confidence: 97%
“…In clinical trials, T replacement has consistently shown improvement in libido (22,30), whereas its efficacy in improving erectile dysfunction remains unclear (31). To our knowledge, no previous randomized controlled trial has assessed the efficacy of T replacement in men with low T and ejaculatory disorders.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, the American College of Physician guidelines recommend PDE5Is as the first-line therapy for erectile dysfunction (Goldstein et al , 1998; Rosen et al , 2002; Qaseem et al , 2009). Nevertheless, the effects of PDE5Is on androgen levels in men with low testosterone remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although head-to-head studies are lacking, the efficacy reported for PDE5 inhibitors is greater than that reported for lifestyle intervention and testosterone treatment (15, 25). The American College of Physicians guidelines emphasize lifestyle and risk factor modification, given that erectile dysfunction is an early marker of cardiovascular risk, recommend PDE5 inhibitors as first-line pharmacotherapy, and judge the evidence for testosterone treatment insufficient to guide definitive recommendations (43). …”
Section: Targeting the Clinical Problemmentioning
confidence: 99%